Calculation of surface tensions for liquid mixtures using the SWCF‐VR EOS and Butler‐type method. Issue 8 (17th May 2019) - Li, Jinlong; He, Changchun; Peng, Changjun; Liu, Honglai
Abstract: A generalized surface tension model for various types of liquid mixtures by coupling the equation of state for square‐well chain fluids with variable ranges and Butler type method was presented. Transferable molecular parameters fitted from experimental pVT of pure fluids were used. The reliability of this model were tested with liquid mixtures including 87 conventional fluid mixtures, 20 aqueous alcohol‐amine solutions, 12 ionic liquid solutions, 7 polymer solutions, and 4 liquid alloys. The overall average absolute deviations in correlations with one parameter for all binary mixtures, in predictions for all conventional binary mixtures except aqueous solutions and for all ternary mixtures are 1.94%, 1.82%, and 2.69%, respectively. The potential application of the model in simultaneously describing the phase equilibrium and surface tensions was partially verified. The results demonstrate that this model has an overall robustness and reliability in calculations of surface tensions for various liquid mixtures.